Use of sewage sludge as supplementary diet for the carp, Cyprinus carpio (L) - Saini, V P; Sharma, L L (Indian Journal of Fisheries, 2011)
Sewage sludge - a common urban refuse was tried as supplementary feed for thefish {Cyprinus carpio L average weight 4.9 g) @ 0, 50, 75 and 100%. The fishwas raised on the experimental diet in plastic containers of 65 1 capacity for 60days. Common carp fed on 100% sewage sludge failed to indicate appreciablegrowth. However, partial replacement (50%) was favourable and resulted in highgrowth (4.58 g). Fish reared with 50% sewage sludge supplemented diet alsoattained high (9.12%) protein level (wet weight basis) as compared to control(9.05%) and other treatments. The bacterial load in the selected body tissues waswell below the safe levels prescribed by WHO for human consumption. The valuesof total coliforms, faecal coliforms, E. coli and streptococci ranged between 0-7,0-3, 0-1 and 0-3 MPN/g respectively in fish skin and muscles